Prostate cancer: germline prediction for a commonly variable malignancy - Bambury, Richard M.; Gallagher, David J. (BJU international, 2012)
What's known on the subject? and What does the study add? Prostate cancer is a heterogeneous disease and biomarkers to predict its incidence and subsequent clinical behaviour are needed to tailor screening, prevention and therapeutic strategies. Rare mutations in genes such as BRCA1, BRCA2 and HOXB13 can affect prostate cancer incidence and/or clinical behaviour. Genome wide association studies (GWAS) have identified more common genetic variations that explain an estimated 20% of familial prostate cancer risk. In this review, we focus on the potential of germline genetic variation to provide biomarkers for prostate cancer screening, prevention and management. We discuss how germline genetics may have a role in treatment selection if reliable pharmacogenetic predictors of efficacy and toxicity can be identified. We have outlined possible mechanisms for including germline investigation in future prostate cancer clinical trials. OBJECTIVES • Prostate cancer is a heterogeneous disease and biomarkers to predict its incidence and subsequent clinical behaviour are needed to tailor screening, prevention and therapeutic strategies. • In this review we focus on the potential of germline genetic variation to provide these biomarkers. METHODS • We review the published literature on germline genetics in prostate cancer and examine the possibility of including germline genetic biomarkers in future prostate cancer clinical trials. RESULTS • Rare mutations in genes such as BRCA1, BRCA2 and HOXB13 can affect prostate cancer incidence and/or clinical behaviour. • Genome‐wide association studies (GWAS) have identified more common genetic variations that explain an estimated 20% of familial prostate cancer risk. • Germline genetics may have a role in treatment selection, if reliable pharmacogenetic predictors of efficacy and toxicity can be identified. CONCLUSION • This rapidly emerging area of prostate cancer research may provide answers to current clinical conundrums in the prostate cancer treatment paradigm. We have outlined possible mechanisms for including germline investigation in future prostate cancer clinical trial design.